2005
DOI: 10.1111/j.1551-2916.2005.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of Electrostatically Stabilized Dispersions of Monodispersed, Bimodal, and Trimodal Silica Particles

Abstract: Effect of particle size and polydispersity on the viscosity and maximum packing fraction of aqueous colloidal dispersions has been studied. For dispersions of mono-sized particles, the results indicate that there is a linear relationship between the log(g) (viscosity) and particle size at a fixed shear rate and volume fraction of solids. However, there is a particle diameter at which there is a decrease in the dependency of viscosity on particle size as the slope of the linear plots of log(g) versus particle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The smaller HA for Al 2 O 3 ceramic suspensions may be attributed to the wider distribution of particle sizes, which provides for a better particle packing and decreases the suspension viscosity. This effect of the viscosity in ceramic suspensions has been reported elsewhere [30].…”
Section: Rheology Of Ceramic Suspensionssupporting
confidence: 79%
“…The smaller HA for Al 2 O 3 ceramic suspensions may be attributed to the wider distribution of particle sizes, which provides for a better particle packing and decreases the suspension viscosity. This effect of the viscosity in ceramic suspensions has been reported elsewhere [30].…”
Section: Rheology Of Ceramic Suspensionssupporting
confidence: 79%
“…The operation mode was set as positive and negative rotation for 8 h. The 5 mm particle size gives the ceramic slurry good uidity, while the 500 nm particle size can reduce the surface defects of the sample during debinding and sintering and improve the density. 24,25 The photosensitive resin can undergo polymerization, cross-linking and curing reaction between monomers to become solid under 405 nm ultraviolet light. The dispersant can prevent the agglomeration of powders and improve the forming quality.…”
Section: Preparation Of the Al 2 O 3 Ceramic Substratementioning
confidence: 99%
“…Previous theoretical and experimental studies have demonstrated that the combination of powders with different particle sizes is an effective method for increasing the volume fraction and reducing the viscosity of the ceramic slurry. Moreover, the density of the sintered body made of powders of different particle sizes is higher than that made of a single particle size powder [16]. Figure 1 shows the complete preparation of the microwave dielectric ceramic filter.…”
Section: Introductionmentioning
confidence: 99%